1991
DOI: 10.1213/00000539-199106000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relation, Neuromuscular Blocking Action, Intubation Conditions, and Cardiovascular Effects of Org 9273, a New Neuromuscular Blocking Agent

Abstract: VAN DEN BROEK L, LAMBALK LM, RICHARDSON FJ, WIERDA JMKH. Dose-response relation, neuromuscular blocking action, intubation conditions, and cardiovascular effects of Org 9273, a new neuromuscular blocking agent. Anesth Analg 1991;72:811-6. The ED,, and the ED,,, the time-course of the neuromuscular block, the intubation conditions, and the cardiovascular effects of Org 9273, a new steroidal nondepolarizing neuromuscular blocking agent, have been evaluated in 41 anesthetized patients. From cumulative dose-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Alternatively, differences in local balance between pre-and post-junctional effects, or in sensitivity of the nicotinic receptors of the various muscle groups could be involved (18,19). Intubation following Org 9273, another new neuromuscular blocking agent, was also possible under good conditions at only partial blockade of the adductor pollicis muscle (20). It seems justified to reconsider the concept that optimal intubating conditions are only provided at neuromuscular block of peripheral muscles equal to or greater than 95% (21).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, differences in local balance between pre-and post-junctional effects, or in sensitivity of the nicotinic receptors of the various muscle groups could be involved (18,19). Intubation following Org 9273, another new neuromuscular blocking agent, was also possible under good conditions at only partial blockade of the adductor pollicis muscle (20). It seems justified to reconsider the concept that optimal intubating conditions are only provided at neuromuscular block of peripheral muscles equal to or greater than 95% (21).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier clinical studies, under similar study conditions, with low potency steroidal compounds, i. e. rocuronium [8], Org 9273 [9] and Org 9487 [5], and in the current study of Org 7617, the time until the first measurable response (20-30 s) approximated the circulation time. Hence, diffusion to the site of action seemed to be rapid and similar to that of succinylcholine [10].…”
mentioning
confidence: 55%
“…In the anaesthetised pig, using a series of 2-morpholino 16-amino (piperidino or pyrrolidino) androstane mono methobromides, it has been demonstrated that changes in the substituent in the 3-position (A-ring) and the 16- (7) 78 (14) 77 (8) 31 (7) 181 (6) 77 (18) 79 (10) 31 (9) 171 (12) 63 (18) 67 (15) the duration of the neuromuscular blockade [2]. This knowledge led to synthesis of a new series of steroidal structures with the anticipated non-depolarizing neuromuscular blocking activity, including Org 7617, the 16-Nallyl, 17-butyrate analogue of vecuronium (Fig.…”
mentioning
confidence: 99%